Kajian Hukum Direksi Perusahaan yang Bertindak sebagai Likuidator dalam Proses Likuidasi Berdasarkan Undang-Undang Perseroan Terbatas (RechtJiva, 2024)
In this thesis, the Author addresses the issue of incomplete norms related to the profession of liquidator in the process of settling company assets under Law Number 40 of 2007 on Limited Liability Companies. The selection of this issue is motivated by the legal uncertainty arising from the lack of comprehensive norms regarding the qualifications required for individuals acting as liquidators in the company asset settlement process, especially when the company's directors are appointed as liquidators. This thesis employs a normative juridical method with a Statute Approach, Conceptual Approach, and Comparative Approach. The author uses grammatical and systematic interpretations in primary, secondary, and tertiary legal materials. Through the research conducted using the aforementioned methods, the author concludes that the normative gap concerning the liquidator profession can be addressed by reconstructing the norms in the Limited Liability Company Law. This includes clarifying the qualifications required for liquidators, which can be demonstrated through official certification, and reconstructing regulations regarding the supervision of liquidators.The comparison between the regulations on liquidation in Indonesia and the United States provides an example of applicable certification for liquidators to reduce the risk of lack of due diligence and to enhance legal certainty and efficiency in the company asset settlement process. This approach can be adopted by adjusting it to the existing asset settlement processes in Indonesia.